2022
DOI: 10.1155/2022/3299146
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and In Vitro Antifungal Activity of Selected Medicinal Plants against Candida albicans and Aspergillus niger in West Shewa Zone, Ethiopia

Abstract: Antimicrobial resistance to commercially available medications has become a global issue, yet there is still the possibility of developing new drugs from medicinal plants. As a result, the aims of the present study were to screen secondary metabolites and to evaluate in vitro antifungal activities of Brucea antidysenterica, Aloe vera, and Justicia schimperiana. After the plants were identified, their leaves were collected, washed, dried under the shade, pulverized, and extracted with methanol (99.8%) using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The antifungal and antibacterial activities of plants extracts might be because of the occurrence of secondary metabolites such as amino acids, terpenoids, tannins, flavonoids, saponins and alkaloids (Gaurav et al, 2019). The variation between the phytochemicals quantified in the current studies and the reported previous studies might be due to many factors such as solventsolute ratio, temperature and period of the extraction process, extraction process solvent, ripening time of fruit, cultivars variations, geographical areas differences, soil composition where herbs grow, seasons of plant collection and growth stage of plants (Sarbaswarup et al, 2019;Askale et al, 2022).…”
Section: Bio Fungicide Potential Of Neemmentioning
confidence: 57%
See 3 more Smart Citations
“…The antifungal and antibacterial activities of plants extracts might be because of the occurrence of secondary metabolites such as amino acids, terpenoids, tannins, flavonoids, saponins and alkaloids (Gaurav et al, 2019). The variation between the phytochemicals quantified in the current studies and the reported previous studies might be due to many factors such as solventsolute ratio, temperature and period of the extraction process, extraction process solvent, ripening time of fruit, cultivars variations, geographical areas differences, soil composition where herbs grow, seasons of plant collection and growth stage of plants (Sarbaswarup et al, 2019;Askale et al, 2022).…”
Section: Bio Fungicide Potential Of Neemmentioning
confidence: 57%
“…These compounds are by nature alkaline and demonstrate pharmacological activities with an extraordinary array (Gaurav et al, 2019). The antimicrobial properties of alkaloids are reported by due to blocking enzyme activity (Askale et al, 2022). Phenols are a class of phytochemicals dispersed in plants that are utilize as antibiotic agents because of their capabilities to break integrity of membrane shape in a diverted manner and stop certain enzymes of electron transport chain (Askale et al, 2022).…”
Section: Bio Fungicide Potential Of Neemmentioning
confidence: 99%
See 2 more Smart Citations
“…Mayer's reagent test method was used to process the extracts (1.36 g of mercuric chloride and 5 g of potassium iodide in 100 ml of water). e presence of alkaloids is indicated by the formation of a yellow-colored precipitate [12].…”
Section: Test For Alkaloidsmentioning
confidence: 99%